A 45-Amino-Acid Scaffold Mined from the PDB for High-Affinity Ligand Engineering. Issue 7 (23rd July 2015) - Kruziki, Max A.; Bhatnagar, Sumit; Woldring, Daniel R.; Duong, Vandon T.; Hackel, Benjamin J.
Summary: Small protein ligands can provide superior physiological distribution compared with antibodies, and improved stability, production, and specific conjugation. Systematic evaluation of the PDB identified a scaffold to push the limits of small size and robust evolution of stable, high-affinity ligands: 45-residue T7 phage gene 2 protein (Gp2) contains an α helix opposite a β sheet with two adjacent loops amenable to mutation. De novo ligand discovery from 10 8 mutants and directed evolution toward four targets yielded target-specific binders with affinities as strong as 200 ± 100 pM, T m s from 65°C ± 3°C to 80°C ± 1°C, and retained activity after thermal denaturation. For cancer targeting, a Gp2 domain for epidermal growth factor receptor was evolved with 18 ± 8 nM affinity, receptor-specific binding, and high thermal stability with refolding. The efficiency of evolving new binding function and the size, affinity, specificity, and stability of evolved domains render Gp2 a uniquely effective ligand scaffold. Graphical Abstract: Highlights: Systematic search of PDB for small, evolvable protein as a binding scaffold Gp2 with 45 amino acids has small size, ease of evolution, and stability De novo discovery of high-affinity, specific Gp2 binders toward four targets Gp2 evolved to target epidermal growth factor receptor Abstract : Kruziki et al. present a small protein scaffold (Gp2) that enables simple de novo ligand discovery and evolution toward multiple targets. Gp2 uniquely combines robust evolution, small size (45 amino acids), nanomolar affinity, and high thermal stability.